Hak Asasi Manusia dalam Al-Qur'an: Analisis Tafsir Tematik dan Relevansinya terhadap Prinsip Hak Asasi Manusia Universal - Muhammad Fikran Said; Muhammad Irham; Rosmini Rosmini; Nurchamidah Nurchamidah; Muhammad Hamsah (Matan : Journal of Islam and Muslim Society, 2026)
Human Rights (HR) is a fundamental issue in social and religious life that has become the focus of various circles, including Islamic studies. This research aims to analyze the concept of Human Rights in the Qur'anic perspective through a thematic interpretation approach (tafsir maudhu'i), identify HR terms in the Qur'an, and examine the relevance of Qur'anic HR concepts to universal human rights principles. This study employs a qualitative method with a thematic interpretation approach, collecting data through library research by examining classical and contemporary tafsir literature, as well as documents related to universal human rights. The analysis uses content analysis techniques to identify patterns and themes related to HR in the Qur'an. The results show that the Qur'an contains fundamental HR concepts manifested through terms such as al-haqq (rights/truth), al-'adl (justice), al-hurriyyah (freedom), al-musawah (equality), and al-karamah (dignity). The Qur'an emphasizes human dignity (Q.S. al-Isra' [17]: 70), equality (Q.S. al-Hujurat [49]: 13), right to life (Q.S. al-Ma'idah [5]: 32), religious freedom (Q.S. al-Baqarah [2]: 256), and social justice. Qur'anic HR concepts have strong relevance to universal HR principles in the Universal Declaration of Human Rights (1948), though with a theocentric approach emphasizing balance between rights and obligations. This research contributes to strengthening understanding that Islam has a value system aligned with universal HR principles, while offering spiritual and moral dimensions that enrich modern HR discourse.